Study on Air Pollution and Its Dispersion Pattern in Pokhara Valley (Pokhara Engineering College Journal, 2025)
Regional International Airport has been in operation in the mid of Pokhara Metropolitan City where most of the farming land has been converted to the built-up area. Distinct temperature difference has been felt in between downtown and nearby sub-urban area. This study was conducted to investigate the wind flow pattern and air pollution dispersion mechanism in Pokhara. A numerical simulation technique such as A2C flow / A2C t & d was introduced to simulate the local wind flow vectors and air pollution (puffs) dispersion by locally generated wind in the study domain. The simulation results for the study domain revealed that the air flows from the mountain region to the valley from the mid-night to the early morning around 8 AM. As the mountain region get heated after the sunshine, the flow velocity decreases and reaches to the transition state around 09:00 – 10:00 AM. Then flow direction changes towards the mountain region after 11 AM and the velocity reaches the maximum around 2 PM to 3 PM. It is continuous till mid-night around 9 PM to 10 PM and again reaches to the transition period. The locally generated wind plays significant role for the transport and dispersion of air pollution (puff) generated from the source to the surrounding region. Generally, urban air pollution generated in the valley area accumulated in the valley region in the mid-night to the early morning and it disperses around the upper air mostly above the mountain region. Mostly, the pollution generated nearby the mountain region disperses above the mountain region in the daytime. Hence it is concluded that the pollution generated from the difference sources such as aviation, automobiles, industries and the construction sites in the periphery of Pokhara Metropolitan City disperses around the Valley and reached up to the nearby mountain region.